Asymptomatic shedding of herpes simplex virus in oral cavity - Abhay Kulkarni; Shruti Wadne; Rajendra Birangane; Rohan Chaudhari; Nitin Kole; Supriya Sankpal (Wolters Kluwer Medknow Publications, 2021)
Herpes simplex virus (HSV) is a significant human pathogen. Dental surgeons and Dental Hygienists come across many patients which are not having clinical symptoms but are the carriers of the disease. The person working in the oral cavity is at high risk for getting infected and also the risk of cross-infection in the general population. Aim: In this study, we determine the prevalence of HSV qualitatively and quantitatively in the oral cavity in apparently asymptomatic patients. Study Setting: Institutional and PCR testing Labs. Methods & Materials: The study analyzed saliva samples derived from 220 individuals which were collected with sterile swabs. The traditional PCR method was done for qualitative analysis and real-time PCR for the quantitative analysis. Results: The results of qualitative analysis showed that HSV-2 was more commonly shed than HSV-1 in the oral cavity, while the infected persons showed more genomic copy numbers. Conclusion: The presence of asymptomatic shedding of HSV-2 may be an indicator of future immunosuppression which should be followed up.